Preterm neonates display altered plasmacytoid dendritic cell function and morphology. Issue 5 (1st May 2013) - Schüller, S. S.; Sadeghi, K.; Wisgrill, Lukas; Dangl, A.; Diesner, S. C.; Prusa, A. R.; Klebermasz‐Schrehof, K.; Greber‐Platzer, S.; Neumüller, J.; Helmer, H.; Husslein, P.; Pollak, A.; et al.
Abstract : Functionality and morphology of pDCs of preterm newborns, with emphasis on TLR9 triggered IFN‐α production. Abstract : Bacterial and viral infections cause high rates of morbidity and mortality in premature newborns. In the setting of viral infection, pDCs play a key role as strong producers of IFN‐α upon TLR9 activation. We analyzed pDC frequency, phenotype, morphology, and function in CB of preterm and term newborns in comparison with adults. Whereas all age groups show similar pDC numbers, BDCA‐2, CD123, and TLR9 levels, the expression of BDCA‐4 and capacity to produce IFN‐α upon TLR9 challenge were decreased significantly in preterm neonates. Furthermore, we show by means of electron microscopy that pDCs from preterm newborns exhibit a distinct, "immature" morphology. Taken together, these findings suggest decreased functionality of pDCs in the premature newborn. The reduced capacity to produce IFN‐α is likely to render such infants more susceptible to viral infections.